Social networks and maintenance of an endangered language: The Kejaman of Malaysia - Amee, Joan; Ting, Su Hie (Emerald Publishing Limited, 2024)
Purpose This study examined how social network influences maintenance of the indigenous language of the Kejaman, a small indigenous group living in Sarawak, Malaysia.